EFEK ANTIBAKTERI DARI EKSTRAK TANDAN PISANG KEPOK (Musa Paradisiaca L.) TERHADAP AKTIVITAS Staphylococcus Aureus - Tutik Maryati; Tristianto Nugoho; Ambar Pertiwiningrum; Zaenal Bachruddin; Raden Lukas Martindro Satrio Ari Wibowo Wibowo; Ragil Yuliatmo (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2020)
ABSTRACT Banana plants are well-known to contain diverse phytochemical compound. This study aimed to identify the antibacterial effects of Kepok Banana bunches (Musa paradisiaca L.) against Staphylococcus aureus bacteria. A laboratory analysis was carried out to determine the zone of bacterial inhibition. The experiment used completely randomized design with 3 treatments (50 µL, 70 µL Kepok Banana bunches extract and 50 µL Chloramphenicol as a positive control), each treatment replicated three times. The study was performed used wells agar diffusion. Data were analyzed by analysis of variance (ANOVA) and followed by Duncan Multiple Range Test (DMRT). Results showed that Kepok Banana bunches had potency as antibacterial agent. Treatments showed different (P<0.05) results in bacterial inhibition zones. Chloramphenicol produces the highest inhibitory zone (34.78 mm), while the difference in the concentration of banana bunches produces the same inhibitory zone (50 µL: 11.52 mm; 70 µL: 15.52). It is concluded that Kepok Banana bunches has potency to use as an antibacterial against Staphylococcus aureus.